Interfuel Substitution. - Serletis, Apostolos (World Scientific, 2012)
Interfuel substitution is an issue that is -- and will likely remain -- an important topic of inquiry for many years, as governments around the world seek to set policies that are intended to restrain carbon emissions or steer economies toward or away from certain fuels. This book contributes to this issue by estimating short- and long-term interfuel substitution elasticities, at the aggregate and sector levels, through the use of the latest advances in microeconometrics as well as recent international data for a number of OECD and non-OECD countries.